Meningkatkan Minat Belajar Siswa Dalam Menulis Teks Prosedur Melalui Media Pembelajaran Audio Visual Kelas VII-2 SMP Pahlawan Nasional Tahun Ajaran 2023/2024 - Luci Banjarnahor; Hotmauli Pandiangan; Novita Hutabalian; Oktavia Simanjuntak; Mustika Wati Siregar (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research aims to increase students' interest in learning in class VII-2 National Hero Middle School in Indonesian language subjects through the use of audio-visual learning media. This research is Classroom Action Research (PTK) which was carried out in two cycles. Data collection was carried out by observation, questionnaires, interviews and documentation. The research results show an increase in students' interest in learning based on the results of observations and questionnaires. At the pre-research stage, observation results showed that students' interest in learning was still low. After implementing audio-visual learning media, students' interest in learning increased. It can be concluded that the use of audio-visual learning media can increase interest in learning Indonesian for class VII-2 students at National Hero Middle School for the 2023/2024 academic year.